Reformulación de un producto cosmético tipo serum a partir de una investigación de mercado (2024)
The cosmetic industry encompasses a booming economic market, and considering segment demand, has ventured into the use of various natural active ingredients. According to the above, it is considered necessary to find products that offer innovative solutions satisfying consumer needs, thus, within innovation processes, validation of new products through research and prior testing is required to determine their sales feasibility. At Icesi University, there is an opportunity for improvement by not having market research that supports all designed products with production potential. For this reason, the reformulation of a serum-type cosmetic product with CBD and Cacay oil is proposed, based on market research. Initially, a market research tool was designed to obtain findings related to texture and fragrance changes in the formulation, secondly, the product was reformulated by adding Novemer and lavender essential oil, and finally, the properties of the obtained formulation were evaluated. A reformulated serum-type cosmetic product was obtained according to market research findings, which has thermal stability for 21 days and has commercial potential for the nascent Cacay oil industry.